Rehabilitasi Sosial Pecandu Narkoba Melalui Terapi Musik dalam Perspektif Hak Asasi Manusia - Hasan, Zainudin; Martinouva, Rissa Afni; Kartika, Kartika; Asnawi, Habib Shulton; Hasanah, Uswatun (Universitas Islam Negeri Raden Intan Lampung, 2022)
Music therapy is the professional use of musical interventions and their elements in a therapeutic relationship to achieve specific goals. Rehabilitation of drug addicts through music therapy is one of the concepts of social rehabilitation by helping to recognize and accept different emotions, develop expressive abilities and self-awareness, increase self-confidence, and facilitate relaxation and reduce stress. The research method used in this research is field research. Based on research conducted by the author at the Way Huwi Narcotics Penitentiary, Lampung Province, using the concept of passive music therapy by only listening to music, the object of research tends to only reach the stage of feeling calm and not yet at the stage of changing mindset significantly to leave old habits and replace them with habits. While the activities carried out in the active music therapy process can include singing, songwriting, improvisation, and performing performances that have therapeutic elements so that the use of active music therapy tends to provide a maximum role rather than just listening. Based on the perspective of human rights, this rehabilitation is in line with the recognition of human rights in the 1945 Constitution which is contained in Article 28A, Article 28C paragraph 1 and then Article 28H paragraph 2.